Analiza sezonowości wybranych procesów gospodarczych - Szmit, Anna (Seasonality analysis of some of economic process, 2006)
A subject of paper is analysis of influence of seasonality method implemented in model over quality of the investigated occurrence description, in which there is trend as well as seasonality. Special intention is paid on time series with multiplicative seasonality. These methods were implemented to decomposition of some economic occurrences with seasonal character.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 562-570